English for speakers of other languages (ESOL) endorsed elementary teachers’ knowledge and practice of culturally and linguistically responsive pedagogy for English learners - Aznar-Mojica, Silvina (Kansas State University, 2020)
Teachers are expected to meet academic, linguistic and cultural needs of English learners (ELs) in general education classrooms. Teachers receive preparation for teaching ELs through pre-service coursework or in-service professional development. The Multicultural Education, Training, and Advocacy, Inc. (META) Consent Decree, in the state of Florida, requires elementary teachers to obtain an English for Speakers of Other Languages (ESOL) endorsement to prepare with knowledge and skills to support ELs. The purpose of this study was to examine ESOL endorsed elementary teachers’ self-reported knowledge and practices, and the relationship between knowledge and practice of culturally and linguistically responsive pedagogy for ELs in general education classrooms. The Survey of ESOL Endorsed Teachers was administered to eighty-three teachers from nine schools in a Florida public school district. Using a mixed methods approach, quantitative findings revealed teachers reported they were sufficiently knowledgeable about all, excepting one, of the principles of culturally and linguistically responsive teaching. Similarly, teachers reported they regularly practiced all, excepting one, of the culturally and linguistically responsive strategies. A positive statistical relationship was evidenced between teachers’ knowledge and practice, excepting knowledge about organizing the classroom so that ELs feel comfortable to learn and grouping ELs with a common native language to support content learning. Findings revealed areas of knowledge and practice that could benefit from enhancement, mainly using ELs native language as a resource in teaching and learning. Qualitative findings revealed ESOL endorsed teachers were culturally sensitive, valued linguistic diversity, scaffolded instruction, and applied strategies for second language acquisition to provide ELs access to learning.
Keywords: English learners; Culturally and linguistically responsive; ESOL endorsed teachers